2001
DOI: 10.1016/s0925-4773(01)00469-5
|View full text |Cite
|
Sign up to set email alerts
|

Vascular expression of Notch pathway receptors and ligands is restricted to arterial vessels

Abstract: Mice with targeted mutations in genes required for Notch signal transduction die during embryogenesis, displaying overt signs of hemorrhage due to defects in their vascular development. Surprisingly, directed expression of a constitutively active form of Notch4 within mouse endothelial cells produces a similar vascular embryonic lethality. Moreover, patients with mutations in Notch3 exhibit the cerebral vascular disorder, cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
266
0
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 392 publications
(285 citation statements)
references
References 16 publications
16
266
0
3
Order By: Relevance
“…We did, for instance, not fully explore the potential involvement of TGF-␤, COUP-TFII, adrenomedullin, or angiopoietins, known to play a role in AV fate decisions. 7,14,22,40 During development and in primary ECs, 52 Notch activation has been associated with endothelial-to-mesenchymal transformation. Despite the ability of hMAPCs to robustly differentiate into SMCs under other conditions ( Figure S1; Document S1), the conditions used for EC differentiation induced SMC differentiation of hMAPCs in vitro and in vivo to a low degree (not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did, for instance, not fully explore the potential involvement of TGF-␤, COUP-TFII, adrenomedullin, or angiopoietins, known to play a role in AV fate decisions. 7,14,22,40 During development and in primary ECs, 52 Notch activation has been associated with endothelial-to-mesenchymal transformation. Despite the ability of hMAPCs to robustly differentiate into SMCs under other conditions ( Figure S1; Document S1), the conditions used for EC differentiation induced SMC differentiation of hMAPCs in vitro and in vivo to a low degree (not shown).…”
Section: Discussionmentioning
confidence: 99%
“…3 Indeed, arteriovenous (AV) specification of ECs is accomplished early in development and is associated with the expression of a specific complement of factors: venous endothelium is characterized by the expression of EphB4, 4 Lefty-1, 5 Lefty-2, 5 COUP-TFII, 6 and MYO1-␤, 5 and arterial ECs express high levels of Notch 1 and 4, 7 Dll-4, 8 EphrinB1 and EphrinB2, 4 Jagged-1 and -2, 7 connexin-40, and Hey-2 (gridlock zebrafish ortholog). 9,10 Studies in Xenopus, zebrafish, and mice have revealed that, besides blood flow, 11 vessel-intrinsic cues and-later in development-signals from outside the vasculature 12,13 are implicated in defining arterial or venous fate such as members of the TGF-␤ pathway, 14,15 VEGF isoforms, 13,[16][17][18] neuropilins, 17 angiopoietins, 19 the Notch pathway, 7,9,[20][21][22] the patched pathway, 20 and COUP-TFII, a member of the orphan nuclear receptor superfamily. 6 Although it has been shown that some of these pathways are well conserved from zebrafish to mouse, less information is available on whether they have a similar role in humans.…”
Section: Introductionmentioning
confidence: 99%
“…There are differences, for example, in growth factor receptor expression between arterial and venous endothelial cells (Moyon et al, 2001;Villa et al, 2001;Wang et al, 1998); in expression of MMPs and TIMP1 between HUVEC and human dermal microvascular endothelial cells (Jackson and Nguyen, 1997); and in ecto-5′-nucleotidase activity between human and porcine endothelial cells (Smolenski et al, 2006). Different endothelial cell types may behave differently in cell culture assays.…”
Section: Endothelial Cell Typesmentioning
confidence: 99%
“…Toutes sont également exprimées dans le système nerveux où elles contrô-lent la destinée et le guidage des précur-seurs neuronaux et des axones, ce qui suggère leur rôle dans l'établissement du réseau vasculaire. Les CE artérielles du poisson zèbre, du poulet et de la souris expriment sélectivement l'éphrine-B2, la neuropiline 1 (NRP1), le récepteur notch3, le ligand de Notch Delta-like 4 et gridlock [5][6][7][8][9][10][11][9][10][11][12][13][14][15][16]. D'autres molécules sont spécifiquement exprimées par les CE veineuses, notamment EphB4, le récepteur du marqueur artériel éphrine-B2 [12].…”
Section: Les Marqueurs Moléculaires Spécifiques Des Artères Et Des Veunclassified